Substituting fish oil with crude palm oil in the diet of Atlantic salmon (Salmo salar) affects muscle fatty acid composition and hepatic fatty acid metabolism - Bell, J Gordon; Henderson, R James; Tocher, Douglas R; McGhee, Fiona; Dick, James R; Porter, Allan R; Smullen, Richard P; Sargent, John R (American Society for Nutritional Sciences, 2002)
Supplies of marine fish oils (FO) are limited and continued growth in aquaculture production dictates that substitutes must be found that do not compromise fish health and product quality. In this study the suitability of crude palm oil (PO) as a replacement for FO in diets of Atlantic salmon was investigated. Duplicate groups of Atlantic salmon postsmolts were fed four practical-type diets in which the added lipid was either 100% FO and 0% crude PO (0% PO); 75% FO and 25% PO (25% PO); 50% FO and 50% PO (50% PO); and 100% PO, for 30 wk. There were no effects of diet on growth rate or feed conversion ratio nor were any histopathological lesions found in liver, heart or muscle. Lipid deposition was greatest in fish fed 0% PO and was significantly greater than in fish fed 50% and 100% PO. Fatty acid compositions of muscle total lipid were correlated with dietary PO inclusion such that the concentrations of 16:0, 18:1(n-9), 18:2(n-6), total saturated fatty acids and total monoenoic fatty acids increased linearly with increasing dietary PO. The concentration of eicosapentaenoic acid [20:5(n-3)] was reduced significantly with increasing levels of dietary PO but the concentration of docosahexaenoic acid [22:6(n-3)] was significantly reduced only in fish fed 100% PO, compared with the other three treatments. Similar diet-induced changes were seen in liver total lipid fatty acid compositions. Hepatic fatty acid desaturation and elongation activities were ∼10-fold greater in fish fed 100% PO than in those fed 0% PO. This study suggests that PO can be used successfully as a substitute for FO in the culture of Atlantic salmon in sea water. However, at levels of PO inclusion above 50% of dietary lipid, significant reductions in muscle 20:5(n-3), 22:6(n-3) and the (n-3):(n-6) PUFA ratio occur, resulting in reduced availability of these essential (n-3) highly unsaturated fatty acids to the consumer.